Handbook of thin film deposition - Seshan, Krishna; Schepis, Dominic (William Andrew, an imprint of Elsevier, 2018)
Handbook of thin film deposition, Fourth edition, is a comprehensive reference focusing on thin film technologies and applications used in the semiconductor industry and the closely related areas of thin film deposition, thin film micro properties, photovoltaic solar energy applications, materials for memory applications and methods for thin film optical processes. The book is broken up into three sections: scaling, equipment and processing, and applications. In this newly revised edition, the handbook will also explore the limits of thin film applications, most notably as they relate to applications in manufacturing, materials, design and reliability. Offers a practical survey of thin film technologies aimed at engineers and managers involved in all stages of the process: design, fabrication, quality assurance, applications and the limitations faced by those processes. Covers core processes and applications in the semiconductor industry and new developments within the photovoltaic and optical thin film industries.